Monetary policy and sectoral bank lending in Malaysia - Abd Karim, Mohd Zaini; Mohd Harif, Mohd Amy Azhar; Abdul Adzis, Azira (Routledge, 2006)
Unlike most studies on the effect of monetary policy on bank lending, this article intends to answer the question whether the tightening of monetary policy in Malaysia before and after the financial crisis in 1997 affected differently the commercial bank lending to various sectors of the economy. To achieve the objective, Vector Autoregressive Regression (VAR) method was used to generate impulse response function and variance decomposition to trace the impact of a shock in monetary policy on bank lending in Malaysia. The results show that a monetary policy tightening in Malaysia gives a negative impact on all the sectors. Analyzing sectoral responses to monetary shocks, evidence is found that some sectors are more affected than the others. The manufacturing, agricultural, and mining sector seems to decline more than the aggregate bank lending in response to interest rate shock.